Pronominalisation in South Asian Languages: of People and their Actions - Bhattacharya, Tanmoy (Nepalese Linguistics, 2018)
By looking at agreement in Indo-Aryan (IA), and Munda languages, it is suggested that the apparent similarity of a certain phenomenon across unrelated languages is not a sufficient condition for contact induced change. In particular, I will investigate the phenomenon of “multiple agreement” in detail in Munda languages to show that it is not the same as agreement in contiguous IA languages.